Harmonizing semantic annotations for computational models in biology - Neal, Maxwell Lewis; König, Matthias; Nickerson, David; Scharm, Martin; Wolkenhauer, Olaf; Waltemath, Dagmar; Mısırlı, Göksel; Kalbasi, Reza; Dräger, Andreas; Atalag, Koray; Chelliah, Vijayalakshmi; Cooling, Michael T.; et al. (Briefings in bioinformatics, 2019)
Abstract. Life science researchers use computational models to articulate and test hypotheses about the behavior of biological systems. Semantic annotation is